Enhanced fatigue and ferroelectric properties in multiferroic (Ba 0.7Sr0.3)TiO3/(Bi1.05La 0.05)FeO3 epitaxial heterostructures - Chew, Khian Hooi; Jiang, Y.; Miao, J.; Xu, X.G.; Zhang, J.X.; Zhan, Q. (AIP Publishing, 2013)
Fatigue and ferroelectric properties of multiferroic (Ba 0.7Sr0.3)TiO3/(Bi1.05La 0.05)FeO3 (BST/BLF) epitaxial heterostructures are studied and compared to those of BLF single-layer films. Our studies show that oxygen vacancies V O • • are the most likely mobile defects in bilayers, whereas defect dipole complexes (F e F e 3 + ′ - V O • •) dominate the single-layer film. However, the fatigue mechanism in both structures is mainly governed by the migration of V O • •. The presence of BST layer in the bilayer increases the energy barrier for the migration of V O • • and decreases the concentration of V O • •. The BST/BLF bilayer reveals an improved fatigue and ferroelectric properties, suggesting a step towards realizing nonvolatile memory applications. © 2013 AIP Publishing LLC.